The role of WNT10B in physiology and disease: A 10-year update - Perkins, Rachel S.; Singh, Rishika; Abell, Amy N.; Krum, Susan A.; Miranda-Carboni, Gustavo A. (Frontiers in Cell and Developmental Biology, 2023)
WNT10B, a member of the WNT family of secreted glycoproteins, activates the WNT/β-catenin signaling cascade to control proliferation, stemness, pluripotency, and cell fate decisions. WNT10B plays roles in many tissues, including bone, adipocytes, skin, hair, muscle, placenta, and the immune system. Aberrant WNT10B signaling leads to several diseases, such as osteoporosis, obesity, split-hand/foot malformation (SHFM), fibrosis, dental anomalies, and cancer. We reviewed WNT10B a decade ago, and here we provide a comprehensive update to the field. Novel research on WNT10B has expanded to many more tissues and diseases. WNT10B polymorphisms and mutations correlate with many phenotypes, including bone mineral density, obesity, pig litter size, dog elbow dysplasia, and cow body size. In addition, the field has focused on the regulation of WNT10B using upstream mediators, such as microRNAs (miRNAs) and long non-coding RNAs (lncRNAs). We also discussed the therapeutic implications of WNT10B regulation. In summary, research conducted during 2012–2022 revealed several new, diverse functions in the role of WNT10B in physiology and disease.